(untitled) (Bon Voyage, 2019)
The article has selected Henry Rider Haggard’s adventure fiction, King Solomon’s Mines, for its eco-feminist critical scrutiny. In so doing, it usurps the working definition of the term "ecofeminism" as a tool of inquiry. Then it demonstrates how the rhetoric of empire constructs and mirrors the African continent in general and people and animals in particular. The article primarily exposes the sinister colonial rhetoric of equating nature - land and animals - with women, thus site for exploration and exploitation opens up. The rhetoric becomes an instrument in defining and understanding them for achieving its political ends which leads to unbridled exploitation of both. The analysis further understands the discursive technique of equating nature and natives to establish the European legitimacy for exploitation of native people and nature.